2010
DOI: 10.1037/a0019944
|View full text |Cite
|
Sign up to set email alerts
|

Group identification as a moderator of the relationship between perceived social norms and alcohol consumption.

Abstract: Previous research has shown that social norms are among the strongest predictors of college student drinking. Among college students, perceiving that "others" drink heavier relative to themselves has been strongly and consistently associated with heavier drinking. Research has also shown that the more specifically "others" are defined, the stronger the association with one's own drinking. The present research evaluated whether group identification as defined by feeling closer to specific groups moderates the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 231 publications
(151 citation statements)
references
References 47 publications
(68 reference statements)
8
143
0
Order By: Relevance
“…Social Identity Theory (Abrams and Hogg, 1999;Terry and Hogg, 1996) suggests that an individual's behavior is governed more greatly by the groups the individual identifi es with or refers to in seeking appropriate normative behavior. Consistent with this perspective, recent fi ndings have shown social identity to moderate the infl uence of perceived norms on drinking (Neighbors et al, 2010;Reed et al, 2007).…”
Section: Religiousness and Alcoholmentioning
confidence: 76%
See 1 more Smart Citation
“…Social Identity Theory (Abrams and Hogg, 1999;Terry and Hogg, 1996) suggests that an individual's behavior is governed more greatly by the groups the individual identifi es with or refers to in seeking appropriate normative behavior. Consistent with this perspective, recent fi ndings have shown social identity to moderate the infl uence of perceived norms on drinking (Neighbors et al, 2010;Reed et al, 2007).…”
Section: Religiousness and Alcoholmentioning
confidence: 76%
“…Personalized normative feedback alone has also been shown to measurably reduce drinking among heavy drinkers for up to 2 years (Neighbors et al, , 2010. Group-based live interactive norms feedback has also been effective in reducing groupspecifi c normative misperceptions and subsequent drinking (Killos et al, 2010;LaBrie et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, investigations have begun to consider the importance of who the "others" are, how they relate to the perceiver, and how these factors might translate into improved strategies for prevention and treatment. Although some research has considered who the "others" are from a subjective standpoint (i.e., quality of the peer relationships or how closely one identifi es with the relevant group; Borsari and Carey, 2006;Neighbors et al, 2010a;Reed et al, 2007), other research has evaluated specifi city as a function of more objectively defi ned group membership based on demographic representation (e.g., Larimer et al, 2009;Lewis and Neighbors, 2006), gender Suls and Green, 2003), and class standing (Pedersen et al, 2010), among other dimensions. The present research represents the most comprehensive evaluation of the infl uence of group specifi city of drinking norms on alcohol consumption to date.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of peer relationships in terms of level of intimacy, stability, and perceived support appears to be important in determining the magnitude and direction of peer infl uences on drinking (Borsari and Carey, 2006). Recent studies found that greater identifi cation with a given group moderates associations between perceived drinking norms for that group and one's own drinking (Neighbors et al, 2010a;Reed et al, 2007).…”
Section: Specifi City Of the Normative Referent Groupmentioning
confidence: 99%
“…In social marketing, this has led to the development of the social norms approach (Cialdini and Goldstein, 2004), a marketing technique that attempts to influence behaviour by changing perceptions of what is normal (Lewis and Neighbors, 2006;Neighbors et al, 2010;Burchell et al forthcoming). According to the literature, this approach has proven successful in influencing bullying (Perkins et al, 2009), substance abuse amongst students (Perkins, 2003;Bosari and Carey, 2003;Berkowitz, 2005;McAlaney and McMahon, 2007;Neighbors et al, 2008;Moreira et al, 2009), household recycling (Shultz, 1999;Nomura et al, 2011), hotel towel re-use , the payment of tax debts (Cabinet Office, 2012) and domestic electricity consumption (Allcott, 2011;Ayres et al, 2009).…”
Section: Introductionmentioning
confidence: 99%